(3NRGfI GdaJGhis - (3GdMfaj , CMeO Hf eMeO Hf CHj HcQ GdMfaj,J (B522 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdYHO GdVYja CMeO Hf eMeO Hf CHj HcQ jbhd deG aQZJ ef JShjO eLeY GdaJGhi GdPi LeYJ ef cJH GdYdeGA GdYXGe s
(3BNQgG (B:s
(3Pdc CTO GdcQGgjI hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3fSNI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs